Pension regimes and saving - Mackenzie, G. A.; Gerson, Philip R.; Cuevas, Alfredo; International Monetary Fund. (Washington, DC : International Monetary Fund, 1997)
This study analyzes the impact of pension systems and pension reform on saving, paying particular attention to the impact of the introduction of defined-contribution plans like that of Chile. It also surveys the literature on the impact of pension regimes on saving, discusses some recent reforms, and addresses the role of private pension plans.
"August 1997."
Includes bibliographical references (p. 41-43).
Keywords: Pension trusts; Old age pensions; Saving and investment; Defined benefit pension plans